Library at Dearborn Chemical Company - Dearborn Chemical Company (1927)
General view of employees at work in the library at the Dearborn Chemical Company 35th Street laboratory facilities located in Chicago, Illinois. The male employees are identified as C.C. Dennis (left) and A.H. Reynolds (right). The female employee seated on the right-hand side is unidentified. Founded in 1887, the Dearborn Chemical Company was a corporate ancestor of BetzDearborn, Incorporated best known for manufacturing water treatment chemicals for use in boilers, cooling towers, and steam locomotives.
Keywords: Employees; Chemical industry; Dearborn Chemical Company; Corporations; Women employees